Evaluación de los parámetros productivos de pollos cobb 500 alimentados con dos balanceados comerciales - Pita Roldán, Manuel Adolfo (2019)
D did not affect the productive response of Cobb 500 chickens under the conditions of the present investigation. The objective of the present investigation was to evaluate the productive performance during the fattening period of Cobb 500 chickens fed with two commercial balances on some productive variables, carcass yield, abdominal fat, degree of tarsal pigmentation and peaks, and Cost / Benefit ratio. The test was carried out in the Pastures and Forages Unit of the Agricultural Polytechnic Higher School of Manabí. Two treatments were defined: Treatment 1 (T1) commercial balanced feed with four food phases and Treatment2 (T2) commercial balanced feed with two food phases. 200 chickens were used for each treatment of one day of age with an initial weight of 42.40g for T1 and of42.95g for T2. The data were analyzed using the 5% Student's T test using InfoStat (2016). The statistical analysis showed no significant differences (p> 0.05) for the variables studied, except for the channel yield variables. The highest degree of tarsal and peak pigmentation was obtained in treatment 1 (p <0.05). The IEE (European efficiency index) for both treatments was classified as good. Regarding the cost-benefit ratio, both treatments presented a positive profit margin. However, the T2 treatment was higher, indicating that for every dollar invested 0.56 cents of profitability were generated. It is concluded that the number of phases of commercial balances employe